2020
DOI: 10.1096/fj.201902102rr
|View full text |Cite
|
Sign up to set email alerts
|

cAMP‐dependent protein kinase inhibits FoxO activity and regulates skeletal muscle plasticity in mice

Abstract: Although we have shown that catecholamines suppress the activity of the Ubiquitin‐Proteasome System (UPS) and atrophy‐related genes expression through a cAMP‐dependent manner in skeletal muscle from rodents, the underlying mechanisms remain unclear. Here, we report that a single injection of norepinephrine (NE; 1 mg kg−1; s.c) attenuated the fasting‐induced up‐regulation of FoxO‐target genes in tibialis anterior (TA) muscles by the stimulation of PKA/CREB and Akt/FoxO1 signaling pathways. In addition, muscle‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 63 publications
(177 reference statements)
2
27
0
Order By: Relevance
“…Some scholars used gene chip technology to screen the related genes of exercise-induced fatigue. They found that the up-regulated genes in quadriceps femoris of exercise-induced fatigue mice included PKA (Silveira et al 2020 ; Gordon et al 2017 ; Caiati et al 2013 ) and other protein kinase genes, which were involved in the occurrence and development of exercise-induced central fatigue (Gordon et al 2017 ). CREB (protein kinase A-cAMP response element-binding protein) is a transcription factor in the nucleus, which can regulate a variety of nervous system functions, such as learning and memory.…”
Section: Nf-κb Regulates Central Nervous System Functional Genes and Affects The Occurrence And Development Of Central Fatiguementioning
confidence: 99%
“…Some scholars used gene chip technology to screen the related genes of exercise-induced fatigue. They found that the up-regulated genes in quadriceps femoris of exercise-induced fatigue mice included PKA (Silveira et al 2020 ; Gordon et al 2017 ; Caiati et al 2013 ) and other protein kinase genes, which were involved in the occurrence and development of exercise-induced central fatigue (Gordon et al 2017 ). CREB (protein kinase A-cAMP response element-binding protein) is a transcription factor in the nucleus, which can regulate a variety of nervous system functions, such as learning and memory.…”
Section: Nf-κb Regulates Central Nervous System Functional Genes and Affects The Occurrence And Development Of Central Fatiguementioning
confidence: 99%
“…As mentioned above, norepinephrine stimulation decreases FoxO1 protein abundance via the cAMP-PKA pathway in murine skeletal muscle [25]. b 2 -AR couples with the G protein, which activates adenylyl cyclase, catalyzing the formation of cAMP [37].…”
Section: Discussionmentioning
confidence: 89%
“…Recently, the injection of norepinephrine was shown to suppress FoxO transcriptional activity via the cAMP-protein kinase A (PKA) pathway, consequently decreasing the expression of Atrogin-1/MAFbx mRNA in murine skeletal muscles [23]. Interestingly, Silveria et al [25] also reported that norepinephrine stimulation induces FoxO1 phosphorylation and decreases FoxO1 protein abundance. The abundance of FoxO protein also has dramatic effects on its own transcriptional activity and/or the functions of its downstream targets [26,27].…”
mentioning
confidence: 99%
“…FOXO transcription factors have a positive effect in proteasome regulation through activation of transcription of proteasome sub-units[ 12 ]. A pathophysiologic role of FOXO transcription factors in muscle atrophy through proteasome genes induction, and reversal of atrophy by protein kinase A inhibition of FOXO members FOXO1 and FOXO3 has been described[ 29 ]. Transcription co-activator Peroxisome Proliferator Activated Receptor gamma Co-activator 1alpha (PGC-1α) counteracts the atrophy promoting effects of FOXO3 and reduces denervation-induced muscle atrophy and cancer cachexia in mice[ 30 ].…”
Section: Regulators Of Proteasome With Focus On Pancreatic Cancermentioning
confidence: 99%